2017
DOI: 10.1016/j.ajog.2017.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Maternal marijuana use, adverse pregnancy outcomes, and neonatal morbidity

Abstract: Background The NICHD Stillbirth Collaborative Research Network (SCRN) previously demonstrated an association between stillbirth and maternal marijuana use as defined by the presence of 11-nor-delta-9-tetrahydrocannabinol-9-carboxylic acid (THC) in the umbilical cord homogenate. However, the relationship between marijuana use and perinatal complications in live births is uncertain. Objective Our aim was to examine if maternal marijuana use is associated with increased odds of adverse pregnancy outcomes and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 30 publications
2
99
0
Order By: Relevance
“…Prenatal cannabis use was also associated with increased admission to a neonatal intensive care unit in four out of six studies (adjusted relative risk, aRR = 1.40, 95% CI 1.36–1.44; aOR = 2.0, 95% CI 1.7–2.5; aOR = 2.0, 95% CI 1.7–2.4; aOR = 1.54, 95% CI 1.14–2.07). Of three additional studies that did not report adjusted effect measures, two found no difference in the prevalence of neonatal intensive care unit admission according to prenatal cannabis use (6.6% in weekly users versus 6.1% in nonusers, P = 0.95; 16.9% versus 9.5%, P = 0.12) . A study by Ko et al .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Prenatal cannabis use was also associated with increased admission to a neonatal intensive care unit in four out of six studies (adjusted relative risk, aRR = 1.40, 95% CI 1.36–1.44; aOR = 2.0, 95% CI 1.7–2.5; aOR = 2.0, 95% CI 1.7–2.4; aOR = 1.54, 95% CI 1.14–2.07). Of three additional studies that did not report adjusted effect measures, two found no difference in the prevalence of neonatal intensive care unit admission according to prenatal cannabis use (6.6% in weekly users versus 6.1% in nonusers, P = 0.95; 16.9% versus 9.5%, P = 0.12) . A study by Ko et al .…”
Section: Resultsmentioning
confidence: 96%
“…After duplicates were removed, 6542 publications were screened by title and abstract. Of these, 109 were retrieved for full‐text review and 41 studies were included in our scoping review …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional retrospective studies have also linked prenatal cannabis exposure to impaired memory, impulse control, problem solving, and quantitative reasoning Lester and Dreher, 1989). However, the interpretation of the human literature is complicated by Maternal cannabis vapor exposure confounding factors, including underreporting of use (Metz et al, 2017) and co-use of other drugs (Qato et al, 2020). Thus, very little is known about the enduring effects of prenatal cannabis exposure, independent of these extraneous factors.…”
Section: Introductionmentioning
confidence: 99%
“…Identification via screening of pregnant women for substance use is necessary to link women who use substances with education, counseling, and other resources that may mitigate risks of drug exposure throughout pregnancy. Marijuana use in pregnancy has been linked to adverse birth outcomes, with some studies finding increased risk of reduced weight for gestational age, preterm labor, and low birthweight . Furthermore, women using marijuana during pregnancy are twice as likely to suffer a stillbirth as compared to women who do not .…”
Section: Introductionmentioning
confidence: 99%